Light at the end of the tunnel: Clinical features and therapeutic prospects of KRAS mutant subtypes in non-small-cell lung cancer - Gao, Liyuan; Shen, Weizhang (Frontiers in Genetics, 2022)
Lung cancer is one of the most common causes of cancer-related deaths, and non-small-cell lung cancer (NSCLC) accounts for approximately 85% of all lung cancer cases. Kirsten rat sarcoma virus (KRAS), one of the three subtypes of the RAS family, is the most common oncogene involved in human cancers and encodes the key signaling proteins in tumors. Oncogenic KRAS mutations are considered the initiating factors in 30% of NSCLC cases, accounting for the largest proportion of NSCLC cases associated with driver mutations. Because effective inhibition of the related functions of KRAS with traditional small-molecule inhibitors is difficult, the KRAS protein is called an “undruggable target.” However, in recent years, the discovery of a common mutation in the KRAS gene, glycine 12 mutated to cysteine (G12C), has led to the design and synthesis of covalent inhibitors that offer novel strategies for effective targeting of KRAS. In this review, we have summarized the structure, function, and signal transduction pathways of KRAS and discussed the available treatment strategies and potential treatment prospects of KRAS mutation subtypes (especially G12C, G12V, and G12D) in NSCLC, thus providing a reference for selecting KRAS mutation subtypes for the treatment of NSCLC.